ANALISIS SISTEM ANTRIAN SEPEDA MOTOR DI SPBU 43.413.32 CIKAMPEK KABUPATEN KARAWANG - Pratama, Fachri Dio; Momon, Ade (Peneliti.net, 2024)
SPBU is a place where people can buy fuel for vehicles such as motorbikes, cars, and so on. SPBU 34-41332 is located in Jalan BIC industrial area, Dawuan Tengah, Cikampek, Karawang. During busy hours such as going home from work, this gas station quite often experiences crowds, this is due to the location of this gas station which is quite strategic because it is located near the industrial area and close to the provincial highway where many motorists pass around this gas station, especially motorcyclists, this queue usually starts to occur from 15.00 WIB and usually starts to return to normal at 20.00 WIB and usually occurs at the pertalite fuel filling station for motorbikes. This study aims to determine whether the level of service and service time at SPBU 34-41332 is at the optimal level using the analysis of the queuing system method with the multiple-line queuing model (M/M/S). The data source obtained is primary data obtained by making direct observations carried out at SPBU 34-41332 and coupled with conducting interviews with several officers in the field to add the required data. The results obtained the average time the customer is in the longest system is in the time period between 15.00 to 16.00 WIB with a length of time of 0.8540 minutes and the average time the customer is in the shortest system is in the period between 13.00 to 14.00 WIB with a length of time of 0.6233 minutes.